Multiplex PCR and Antibiotic Use in Children with Community-Acquired Pneumonia - Teresa del Rosal; Patricia Bote-Gascón; Iker Falces-Romero; Talía Sainz; Fernando Baquero-Artigao; Paula Rodríguez-Molino; Ana Méndez-Echevarría; Blanca Bravo-; Luis A. Alonso; Cristina Calvo (MDPI AG, 2024)
Antibiotics are frequently prescribed to children with pneumonia, although viruses are responsible for most cases. We aimed to evaluate the impact of multiplex polymerase chain reaction (mPCR) on antibiotic use. We conducted a prospective study of children under 14 years of age admitted for suspected viral pneumonia, from October 2019 to June 2022 (except March-November 2020). A mPCR respiratory panel (FilmArray® 2plus, bioMérieux, Marcy-l'Étoile, France) was performed within 72 h of admission. Patients with positive reverse transcription PCR for respiratory syncytial virus, influenza, or SARS-CoV-2 were excluded. We compared the patients with historical controls (2017-2018) who had suspected viral pneumonia but did not undergo an aetiological study. We included 64 patients and 50 controls, with a median age of 26 months. The respiratory panel detected viral pathogens in 55 patients (88%), including 17 (31%) with co-infections. Rhinovirus/enterovirus (n = 26) and human metapneumovirus (n = 22) were the most common pathogens, followed by adenovirus and parainfluenza (n = 10). There were no statistically significant differences in the total antibiotic consumption (83% of cases and 86% of controls) or antibiotics given for ≥72 h (58% vs. 66%). Antibiotics were prescribed in 41% of the cases and 72% of the controls at discharge (p = 0.001). Ampicillin was the most commonly prescribed antibiotic among the patients (44% vs. 18% for controls, p = 0.004), while azithromycin was the most commonly prescribed among the controls (19% vs. 48% for patients and controls, respectively; p = 0.001). Our findings underscore the need for additional interventions alongside molecular diagnosis to reduce antibiotic usage in paediatric community-acquired pneumonia.